Venous Thromboembolism Prophylaxis and The International Medical Prevention Registry on Venous Thromboembolism (IMPROVE) Score in Medical Illness Patients - Dania Artriana Riswandi; Amaylia Oehadian (Faculty of Medicine Universitas Padjadjaran, 2020)
Objective: To describe applicability of The International Medical Prevention Registry on Venous Thromboembolism (IMPROVE) score to implement venous thromboembolism prophylaxis in patients with medical illness in Hasan Sadikin General Hospital Bandung.Methods: This study was descriptive, cross-sectional research from database was performed on December 2018. Inclusion criteria in this study were all patients hospitalized in Department of Internal Medicine, Hasan Sadikin General Hospital in November 2018 with medical illness, which is patients with medical condition involves a more systemic, pharmaceutical approach to treatment. Exclusion criteria were surgical disease, which is requires some form of intervention such as surgery, also patients with incomplete medical record were excluded.Results: There were 162 patients (56% male and 44% female). Median age were higher in males compared to females (53 [18-76] vs. 49 [18-85]) years. Low-risk (score <2), medium-risk (score 2 – 3), and high-risk (score >4) for IMPROVE venous thromboembolism score were 77.2%, 17.3%, and 5.6% respectively. ). Low-risk (score <7) and high-risk (score >7) for IMPROVE bleeding score were 75.9% and 24.1% respectively. Medical thromboprophylaxis were given to 14.8% patients, with 91.7% and 8.3% of the patients received unfractionated heparin (UFH) and low-molecular weight heparin (LMWH) respectively. Thromboprophylaxis was given in 88.9% of high-risk patients for venous thromboembolism. There were 18.7% patients with low-risk and 2.6% with high-risk for bleeding that received prophylaxis.Conclusion: The majority of inpatients treated with thromboprophylaxis had low-risk for both thromboembolism and bleeding. The rate of thromboprophylaxis usage was still low; with the most frequently used thromboprophylaxis agent was UFH. Most of high-risk patients for venous thromboembolism received thromboprophylaxis.